Desempenho e características de carcaça de cordeiros ½ Dorper + ½ Santa Inês abatidos com diferentes espessuras de gordura subcutânea - Nascimento, Urias Fagner Santos (2017)
The objective of this study was to evaluate the effect of different subcutaneous fat thicknesses on slaughter in ½ Dorper + ½ Santa Inês lambs on performance (days of confinement, age at slaughter, initial live weight, final live weight, total weight gain, weight gain daily, live weight at slaughter, body condition score), the quantitative characteristics of the carcass (empty body weight, warm carcass weight, cold carcass weight, cooling losses, carcass pH 0 and 24 hours after slaughter, yield carcass yield in the refrigerator, commercial carcass yield, true carcass yield, subcutaneous fat thickness, carcass compatability index, croup width, leg length and leg compatability index) and the characteristics of the carcass. commercial cuts (weights, yields and tissue composition). Twenty-four recently weaned lambs with a mean age of 86 days were used. In the work the animals had their thickness of subcutaneous fat evaluated by ultrasonography at the height of the 12th rib of the left antimer of the animal. After weaning the lambs were allocated in three experimental groups, with the subcutaneous fat thickness at slaughter as treatment (2mm, 3mm and 4mm). After division of the groups the lambs were fed corn silage at will and 2% of the body weight of a mixture with 75% ground corn, 19% soybean meal, 1% urea and 5% commercial core. After the treatment was started, the animals were evaluated biweekly with the aid of an ultrasound device, until they reached the predetermined fat thickness for slaughter. Once this fat thickness was reached, the animals were again weighed to obtain the live weight at the origin, calculated the days of confinement and measured the body condition score, being sent to the slaughterhouse. After 18 hours in solids fasting the animals were again weighed to obtain live weight at slaughter. The experimental design was a completely randomized design with three treatments and eight replicates. Statistical analysis was performed using the SPM GLM procedure. For comparison of means the significance level of 5% was considered by the Tukey test. There was no effect of the treatments (p> 0.05) on the initial live weight, carcass pH immediately after slaughter and 24 hours afterwards, internal carcass length and leg compactness index. However, the confinement days, age at slaughter, final live weight, total weight gain, daily weight gain, live weight at slaughter (p <0.05) as a function of fat thickness for subcutaneous fat thickness by ultrasonography differed , body condition score, weight of the gastrointestinal content, empty body weight, warm carcass weight, cold carcass weight, cooling weight losses, carcass yield at the origin, carcass yield in the refrigerator, commercial yield of the carcass, yield true of carcass, carcass compactness index, croup width, leg length. The percentage of cuts in relation to half carcass; neck (5.62%); shoulder (18.49%), ribs (29.16%), loin (12.15%) and leg (34.91%) did not differ between the GBS (p <0.05). The weights of the cuts presented statistical differences between treatments (p <0.05). As for the tissue composition of the cuts, only the neck muscles, neck bone, loin bones and leg bones presented a statistical difference between the thicknesses of subcutaneous fat (p <0.05). Other tissues (fat, bones, residue and muscle) showed no differences in other cuts. Due to better yields of cuts and carcass, in addition to satisfactory average daily weight gain, it is recommended to slaughter ½ Dorper + ½ Santa Inês lambs with 4mm thick subcutaneous fat.